Implementation of a smoke‐free policy in an inpatient psychiatric facility: Patient‐reported adherence, support, and receipt of nicotine‐dependence treatment. (13th May 2015) - Stockings, Emily A.; Bowman, Jenny A.; Bartlem, Kate M.; McElwaine, Kathleen M.; Baker, Amanda L.; Terry, Margarett; Clancy, Richard; Knight, Jenny; Wye, Paula M.; Colyvas, Kim; Wiggers, John H.
Abstract The implementation of smoke‐free policies in inpatient psychiatric facilities, including patient adherence, mental health nursing staff support, and provision of nicotine‐dependence treatment to patients, has been reported to be poor. The extent to which the quality of smoke‐free policy implementation is associated with patient views of a policy is unknown. We conducted a cross‐sectional survey of 181 patients (53.6%, n = 97 smokers; and 46.4%, n = 84 non‐smokers) in an Australian inpatient psychiatric facility with a total smoke‐free policy. Smokers' adherence to the policy was poor (83.5% smoked). Only half (53.6%) perceived staff to be supportive of the policy. Most smokers used nicotine‐replacement therapy (75.3%); although few received optimal nicotine‐dependence treatment (19.6%). Overall, 45.9% of patients viewed the smoke‐free policy in the unit as positive (29.9% smokers; 64.3% non‐smokers). For smokers, adhering to the ban, perceiving staff to be supportive, and reporting that the nicotine‐replacement therapy reduced cravings to smoke were associated with a more positive view towards the smoke‐free policy. These findings support the importance of patient adherence, mental health nursing staff support, and adequate provision of nicotine‐dependence treatment in strengthening smoke‐free policy implementation in inpatient psychiatric settings.